Antibiotic resistance patterns of bacterial isolates from raw milk sold in coolers in Kawuku, Entebbe, Wakiso district. - Mubangizi, Egidio; Mabonga, Habert (Student’s Journal of Health Research Africa, 2025)
Background: Milk is an essential animal-derived food that provides proteins, vitamins, and minerals vital for human growth and metabolism. However, raw milk is a major vehicle for foodborne pathogens. This study aimed to determine the resistance patterns of pathogenic bacterial species in raw milk sold in coolers in Kawuku Entebbe Wakiso District. Methodology: This laboratory-based cross-sectional study aimed to determine the prevalence of bacterial pathogens and their antimicrobial resistance patterns in raw milk sold from coolers in Kawuku. A total of 20 raw milk samples were aseptically collected from selected milk stalls between January and February 2025 and analyzed using standard microbiological techniques. Bacterial identification was carried out through culture, Gram staining, and biochemical tests, while antimicrobial susceptibility testing was performed using the Kirby–Bauer disc diffusion method in accordance with CLSI guidelines. Results: Staphylococcus saprophyticus (23.3%) and Escherichia coli (16.7%) were the most prevalent pathogens, followed by Klebsiella pneumoniae and Proteus mirabilis (10.0% each). Other bacteria, including S. aureus, E. faecalis, and Citrobacter freundii, were also detected in varying proportions. Antimicrobial susceptibility testing demonstrated high resistance to Cefoxitin (CX5), Tetracycline (TE30), and Penicillin G (P10), while Ciprofloxacin (CIP5), Vancomycin (VA30), and Levofloxacin (LEV15) exhibited higher efficacy. Resistance patterns varied significantly across organisms and media types, with Gram-negative isolates showing more resistance to commonly used antibiotics. Conclusion: Raw milk sold in Kawuku is contaminated with multiple pathogenic bacteria exhibiting significant antimicrobial resistance. Recommendation: Further molecular-level studies are recommended to understand the genetic mechanisms driving resistance.